Monodora myristica (African nutmeg) modulates redox homeostasis and alters functional chemistry in sickled erythrocytes. (May 2018) - Erukainure, OL; Ajiboye, JA; Abbah, UA; Asieba, GO; Mamuru, S; Zaruwa, MZ; Manhas, N; Singh, P; Islam, MS
The antioxidative effect of Monodora myristica seed acetone extract and its effect on chemical functional groups were investigated in sickled erythrocytes as well as molecular modeling of the antisickling potentials of its secondary metabolites. The extract was subjected to gas chromatography–mass spectrometry to identify the compounds present, which were then docked into the allosteric-binding site of deoxy-hemoglobin. The extract was incubated with sickled erythrocytes at 37°C for 6, 12, and 24 h and were subjected to antioxidative analysis for reduced glutathione (GSH), superoxide dismutase (SOD), catalase, and lipid peroxidation (LPO). Chemical functional group of the treated cells was analyzed via Fourier transform infrared spectroscopy (FTIR). The predominant compounds identified were 17-octadecynoic acid; oleic acid, androstan-3-one, 17-hydroxy-2-methyl- (2.beta., 5.beta., 17.beta.)-; estran-3-one, 17-(acetyloxy)-2-methyl-, (2.alpha., 5.alpha., 17.beta.), and (+)-3-carene, 10-(acetylmethyl)-. They all fitted well within the active site of Hb with good binding affinity, as evidenced by the negative CDocker interaction energies of their complexes ranging between −54.4 and −26.7 kcal/mol. Treatment with the extract exacerbated SOD and catalase activities as well as GSH level, while LPO was suppressed. This antioxidative activity was time and/or dose dependent, with 6 and 12 h incubation showing the optimum activity. FTIR analysis of the treated cells showed the presence of hydrophobic functional groups. The synergetic molecular interaction of the major compounds of the extract with the α-dimer of Hb depicts an antisickling effect of M. myristica acetone extract. This is accompanied by exacerbation of endogenous antioxidant enzymes activity and modification of the functional chemistry of the cells.